2014
DOI: 10.1038/srep06156
|View full text |Cite
|
Sign up to set email alerts
|

High Speed All Optical Nyquist Signal Generation and Full-band Coherent Detection

Abstract: Spectrum efficient data transmission is of key interest for high capacity optical communication systems considering the limited available bandwidth. Transmission of the high speed signal with higher-order modulation formats within the Nyquist bandwidth using coherent detection brings attractive performance advantages. However, high speed Nyquist signal generation with high order modulation formats is challenging. Electrical Nyquist pulse generation is restricted by the limited sampling rate and processor capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…The ideal Nyquist filter that provides zero ISI, have a rectangular spectrum and a bandwidth equal to the symbol rate [64], [75]. High speed Nyquist signal generation is challenging, as the electrical pulse generation is restricted by the sampling rate and the bandwidth of DACs as well as the processing capabilities [76]. Super-flat optical frequency combs, with a rectangular spectrum and linear phase, can provide high quality Nyquist pulses [75].…”
Section: B Advantages and Applications Of Mw Sources In Flex-grid Nementioning
confidence: 99%
See 3 more Smart Citations
“…The ideal Nyquist filter that provides zero ISI, have a rectangular spectrum and a bandwidth equal to the symbol rate [64], [75]. High speed Nyquist signal generation is challenging, as the electrical pulse generation is restricted by the sampling rate and the bandwidth of DACs as well as the processing capabilities [76]. Super-flat optical frequency combs, with a rectangular spectrum and linear phase, can provide high quality Nyquist pulses [75].…”
Section: B Advantages and Applications Of Mw Sources In Flex-grid Nementioning
confidence: 99%
“…In [75], Soto et al demonstrated the generation of optical sinc-shaped Nyquist pulses of exceptional quality, using flat rectangular frequency combs, providing zero roll-off, minimum post-modulation spectral broadening and 1% deviation from ideal sinc shape. The authors in [76] demonstrated full band coherent detection of Nyquist pulses employing QPSK modulation and optical time division multiplexing (OTDM). Similarly, sinc-shape pulses can also be multiplexed in the frequency domain, following Nyquist WDM transmission scheme, where pulses can be generated and modulated for each carrier.…”
Section: B Advantages and Applications Of Mw Sources In Flex-grid Nementioning
confidence: 99%
See 2 more Smart Citations
“…Nakazawa et al have also proposed a "Nyquist Laser" with spectral shaping inside the mode-locked cavity [12], which produces similar sinc-shaped pulses. Zhang et al have recently built a single wavelength OrthTDM system using comb lines generated by a CW laser with external modulator and filter, followed by a modulator then an optical OrthTDM multiplexer similar to Nakazawa's arrangement, but using a coherent receiver [13].…”
Section: Introductionmentioning
confidence: 99%